"And How Pretty They Are!": Lawn Tennis, Tourism, and Gender Relations at Niagara-on-the-Lake, Ontario, 1880s-1920s. (January 2023) - Lake, Robert J.
In the four decades straddling the turn of the nineteenth century, the small Ontario town of Niagara-on-the-Lake experienced marked growth in its tourism industry. Catering predominantly to wealthy upper-middle-class Canadian and American visitors, the lake-side settlement offered numerous opportunities for polite recreation. Chief among them was lawn tennis, a sport that sat somewhat outside of the mainstream in terms of its high-class, mixed-sex participation demographic. While its players were imbued with a strong amateur philosophy, local boosters recognized the sport's potential to generate tourism income through its two tournaments, but this hinged on the outward presentation among its players/guests of refined gentility—a reflection of both class and gender—both on and off the court. This article considers how lawn tennis tournaments fit into the town's burgeoning tourism industry, and examines gender relations—particularly the role of women—in relation to this development.